2013
DOI: 10.1038/ncomms3187
|View full text |Cite
|
Sign up to set email alerts
|

Impact tolerance in mussel thread networks by heterogeneous material distribution

Abstract: The Mytilidae, generally known as marine mussels, are known to attach to most substrates including stone, wood, concrete and iron by using a network of byssus threads. Mussels are subjected to severe mechanical impacts caused by waves. However, how the network of byssus threads keeps the mussel attached in this challenging mechanical environment is puzzling, as the dynamical forces far exceed the measured strength of byssus threads and their attachment to the environment. Here we combine experiment and simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 28 publications
0
60
1
Order By: Relevance
“…The combination of multiple phases provides several lines of defence to prevent catastrophic failure during repetitive high-energy loading events. Such clever combinations of material phases across scales are not isolated to stomatopods, or multiscale effects, but emergent mechanofunctionalities can also be attributed to a fine-tuned proportion of materials at a single scale as demonstrated by the impact tolerance of mussel thread networks 42 (Box 1).…”
Section: Multiscale and Multiphasic Organizationmentioning
confidence: 99%
“…The combination of multiple phases provides several lines of defence to prevent catastrophic failure during repetitive high-energy loading events. Such clever combinations of material phases across scales are not isolated to stomatopods, or multiscale effects, but emergent mechanofunctionalities can also be attributed to a fine-tuned proportion of materials at a single scale as demonstrated by the impact tolerance of mussel thread networks 42 (Box 1).…”
Section: Multiscale and Multiphasic Organizationmentioning
confidence: 99%
“…From the late 1990s, researchers also began to find that the threads contained high concentrations of transition metals, like iron and manganese, which interact with catechol groups to cross-link the byssal proteins and make them more cohesive (4). In July, researchers reported that the particular blend of hard and soft materials in the byssal threads helps the mussels to withstand dynamic forces that are nine-times as great as the static strength of the threads (5).…”
Section: Protein Soupmentioning
confidence: 99%
“…Such features include the byssal threads, thin and extensible [7] collagen-reinforced fibres, connected to a flat and wide plaque into which the collagen microfibrils penetrate. Each plaque-thread system exhibits strong plaque-substrate adhesion with a detachment force approximately 2 N as measured upon quasi-static tension [8].…”
Section: Introductionmentioning
confidence: 99%